Outcomes of SARS-Cov-2 infection after COVID-19 vaccination in 1730 hospital admitted cases – An observational study from a tertiary care indian hospital - Amit Roy; Gargi Dey (Apollo Medicine)
Background and Aims: This study aimed to ascertain a number of SARS-CoV-2 infections in patients who had received either dose of vaccination, admitted in a tertiary care center, in New Delhi, and make a comparison with morbidity and mortality. Methods: Data were collected from COVID-19 patients admitted from April 1, 2021, to May 31, 2021. It included the type of vaccination (ChAdOx1 nCoV-19 or BBV152) and the number of doses taken. Mortality and morbidity data were collected and compared based on the computed tomography (CT) severity score. Results: Among 1730 patients, 477 (27.5%) were vaccinated, of which 389 received ChAdOx1 nCoV-19 and 63 received BBV152 vaccine. In 46 patients with breakthrough infection, 7 succumbed. Observed mortality rate was 11.4% (197), of which 53 received a single dose, 11 were completely vaccinated, and 144 were unvaccinated. Among patients who took only one dose, CT severity was mild in 24, moderate in 131, and severe in 27 cases. In fully vaccinated, it was mild in 7, moderate in 22, and severe in just 1 case. Among unvaccinated, 53 had a mild, 349 moderate, and 67 a severe score. Comorbidities were noted in 103 expired patients. Conclusions: The study shows that <30% of patients were vaccinated. Only a handful had completed both doses. Reassuringly, only one among the fully vaccinated had a severe CT score. Although comorbidity influences the prognosis, most of the completely vaccinated who succumbed had no comorbidity. Hence, more research and larger data need to be gathered regarding postvaccination COVID-19 infection.